PENGEMBANGAN POTENSI WISATA MELALUI DAYA TARIKWISATA: (STUDI WISATA KAMPOENG VIETNAM LAMPUNG) - Ningsih, Devi Indri; Aprilani, Deddy; Saptiani, Fenny (Jurnal Kompetitif Bisnis, 2023)
ABSTRACT The study aims to learn the potential development of "kampoeng Vietnam lampung" tourism through tourist attraction. As for the research used on this study using qualitative research methods with qualitative descriptive. Using data-collection techniques in between observation, interview, and documentation. The study has resulted in an image of the potential for natural tourism and a special interest that attracts attraction. The development of a tourist attraction is 4a attractions, shown by a type of live musical attraction (karokean), a coffee band, and an old band with varying attractions provided by the tourist management to make increased tourist visitations. Access (accessibility) with results shows access to social media information, road conditions, the clipboard. Facilities with results indicate they are quite well and complete (mushola, restaurant, gazebo or saung, children's playground, photo spot, and toilet). Additional services that the ancillary service with results showed that there were (pharmacies, hospitals, inns, gas stations, community centers, and ATM machines) complete and close to the Vietnam popoeng tourist attraction.